Implikasi Prinsip Ekonomi Syari’ah dalam Penyusunan Akad Qardh pada Kelompok Pemodal 13 Kec. Pontianak Timur - Hijrah Wahyudi; yudihwy@yahoo.co.id (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2019)
Purpose of this research is to know implication of syari’ah principle in qardh’s contract arrangement inKelompok Pemodal 13 Kec.Pontianak Timur. To answer purpose of the research is done by qualitativeanalysis. This research done to members and managements Kelompok Pemodal 13 Kec. Pontianak Timur,where drawdown of sample is done with technique convenience sampling.Based on result of qualitative analysis indicates that eight syari’ah principle in qardh’s contractarrangement: independence and open system contract, equality, justice, consensuak, honesty and truth,benefit, and trusteeship